2005
DOI: 10.1037/0021-843x.114.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Insomnia.

Abstract: This investigation compared the likelihood of insomnia and insomnia-related health consequences among individuals of different socioeconomic status. A random-digit dialing procedure was used to recruit at least 50 men and 50 women in each age decade from 20 to 80+ years old. Participants completed 2 weeks of sleep diaries as well as questionnaires related to fatigue, sleepiness, and psychological distress. Socioeconomic status was measured by education status assessed at 3 different levels: individual, househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 44 publications
8
81
3
Order By: Relevance
“…The results of other investigators of associations between insomnia and female gender are extended by the findings of this study, confirming that female population relates to higher risk for insomnia (Katz & McHorney, 1998;Roberts et al, 2008;Sutton et al, 2001;Su et al, 2004). Gellis et al (2005) also found that risk for insomnia was significantly greater with increasing age and among women. Katz and McHorney (1998) did not observe a significant association between smoking status and insomnia.…”
Section: Bootstrapsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of other investigators of associations between insomnia and female gender are extended by the findings of this study, confirming that female population relates to higher risk for insomnia (Katz & McHorney, 1998;Roberts et al, 2008;Sutton et al, 2001;Su et al, 2004). Gellis et al (2005) also found that risk for insomnia was significantly greater with increasing age and among women. Katz and McHorney (1998) did not observe a significant association between smoking status and insomnia.…”
Section: Bootstrapsupporting
confidence: 77%
“…Sutton, Moldofsky, and Badley (2001) Others employ 6-month scales (Gellis et al, 2005;Riedel, Durrence, Lichstein, Taylor, & Bush, 2004;Taylor et al, 2007). One-month or four-week insomnia is used as a dependent variable in multivariate techniques in studies conducted by McHorney (1998), Kim et al (2001), and Liu et al (2000).…”
Section: Defining Insomniamentioning
confidence: 99%
“…These include demographic and personal characteristics (e.g. being female [12], older age [13][14][15][16], lower education/socioeconomic status [17][18][19], being divorced/single [20], obesity [21,22]), unhealthy behaviors (e.g. low physical activity [15,23,24], alcohol intake [25,26], smoking [27][28][29][30][31]), poor physical health [32,33] and physical symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Objective measures of SEP, including lower income, education, and occupation status, have been linked to a greater subjective need for sleep (Ursin, Bjorvatn, & Holsten, 2005), greater difficulty initiating and maintaining sleep (Gellis et al, 2005;Hall, Bromberger, & Matthews, 1999;Lauderdale et al, 2006), considerably more accumulated sleep debt (Hall et al, 1999;Ursin et al, 2005), as well as both long (≥ 9 hr) and short (≥ 6 hr) sleep durations (Krueger & Friedman, 2009;Stamatakis, Kaplan, & Roberts, 2007;Stranges et al, 2008;Ursin et al, 2005), even after controlling for important covariates (e.g., gender, age, marital status, and smoking). Objective SEP broadly encompasses contextual factors related to access to tangible resources (Operario et al, 2004).…”
mentioning
confidence: 99%